Study of clinical profile, risk factors of acute kidney injury in children admitted in pediatric intensive care unit at tertiary health care centre - S., Harsha; Mevundi, Gonesh N. (International Journal of Contemporary Pediatrics, 2020)
Background: Acute kidney injury (AKI) is an important condition in hospitalized patients, associated with adverse short- and long-term outcomes. Objective of this study was to determine the clinical profile of acute kidney injury in pediatric ICU (Basaveshwar Teaching and General Hospital, Sangameshwar Hospital, Kalaburagi). Methods: This study was conducted in all patients within the age group of 1 month to 18 years admitted in the PICU (pediatric intensive care unit) at Basaveshwar teaching and General hospital and Sangameshwar hospital attached to Mahadevappa Rampure medical college during a period from December 2015 to May 2017. Results: Incidence of AKI was 6.9% in pediatric intensive care unit. The median age of boys and girls were 4.56±3.84 and 4.49±4.01 respectively. Hypotension and need for ventilation were significant risk factors for AKI (p<0.001). The median admission serum creatinine value in AKI patients was 2.91±2.48 mg/dL. In the present study, the median duration of PICU and Hospital stay was 9.98±7.27 in AKI group compared to7.41±5.62 days in non-AKI group (p<0.001). Conclusions: It was concluded that Incidence of AKI was 6.9% in pediatric intensive care unit. The mean and SD of age of boys and girls were 4.56±3.84 and 4.49±4.01 respectively. Hypotension and need for ventilation were significant risk factors for AKI.